Review of Gardella & Vecchio, Amantes rivales. Sobre la filosofía. Diálogo pseudo-platónico (2017) (Revista Archai, 2019)
Review of Gardella & Vecchio, Amantes rivales. Sobre la filosofía. Diálogo pseudo-platónico (2017)